Penanganan Keluhan, Kualitas Pelayanan, Kepuasan Pelanggan - Della Shafira; Susi Indriyani; Desi Derina Yusda (Lembaga Penelitian, dan Pengabdian Kepada Masyarakat (LPPM) STIE GENTIARAS Bandar Lampung dan berkolaborasi dengan Ikatan Akuntan Indonesia Kompartemen Akuntan Pendidik (IAI KAPd), 2026)
The increasing number of customer complaints from PDAM Way Rilau Bandar Lampung indicates the need to evaluate complaint handling and service quality to improve customer satisfaction. This study aims to analyze the influence of complaint handling and service quality on customer satisfaction at PDAM Way Rilau. The study used a quantitative approach with a survey method involving 381 respondents selected through purposive sampling from 53,029 active customers. Data were collected using a questionnaire and analyzed using multiple linear regression using SPSS version 20. The results showed that complaint handling had a positive and significant effect on customer satisfaction (β = 0.384; t = 4.139; p < 0.001), as did service quality (β = 0.471; t = 6.008; p < 0.001). Simultaneously, both variables significantly influenced customer satisfaction (F = 106.224; p < 0.001) with a coefficient of determination (R²) of 0.360. These findings indicate that service quality and effective complaint handling are important factors in increasing customer satisfaction. Theoretically, this study strengthens the public service management literature by confirming that service quality and complaint handling are the primary determinants of customer satisfaction in regional water service providers.